Refractory out-of-hospital cardiac arrest with ongoing cardiopulmonary resuscitation at hospital arrival – survival and neurological outcome without extracorporeal cardiopulmonary resuscitation - Gregers, Emilie; Kjærgaard, Jesper; Lippert, Freddy; Thomsen, Jakob H.; Køber, Lars; Wanscher, Michael; Hassager, Christian; Søholm, Helle (Critical care (London, England), 2018)
Background The prognosis in refractory out-of-hospital cardiac arrest (OHCA) with ongoing cardiopulmonary resuscitation (CPR) at hospital arrival is often considered dismal. The use of extracorporeal cardiopulmonary resuscitation (eCPR) for perfusion enhancement during resuscitation has shown variable results. We aimed to investigate outcome in refractory OHCA patients managed conservatively without use of eCPR. Methods We included consecutive OHCA patients with refractory arrest or prehospital return of spontaneous circulation (ROSC) in the Copenhagen area in 2002–2011. Results A total of 3992 OHCA patients with resuscitation attempts were included; in 2599, treatment was terminated prehospital, and 1393 (35%) were brought to the hospital either with ROSC ( n = 1285, 92%) or with refractory OHCA ( n = 108, 8%). Of patients brought in with refractory OHCA, 56 (52%) achieved ROSC in the emergency department. There were no differences between patients with refractory OHCA or prehospital ROSC with regard to age, sex, comorbidities, or etiology of OHCA. Time to emergency medical services (EMS) arrival was similar, whereas time to ROSC (when ROSC was achieved) was longer in refractory OHCA patients (EMS, 6 (5–9] vs. 7 [5–10] min, p = 0.8; ROSC, 15 [9–22] vs. 27 [20–41] min, p < 0.001). Independent factors associated with transport with refractory OHCA instead of prehospital termination of therapy were OHCA in public (OR, 3.6 [95% CI, 2.2–5.8]; p < 0.001), witnessed OHCA (OR, 3.7 [2.0–7.1]; p < 0.001), shockable rhythm (OR, 3.0 [1.9–4.7]; p < 0.001), younger age (OR, 1.2 [1.1–1.2]; p < 0.001), and later calendar year (OR, 1.4 [1.2–1.6]; p < 0.001). Thirty-day survival was 20% in patients with refractory OHCA compared with 42% in patients with prehospital ROSC ( p < 0.001). Four of 28 refractory OHCA patients with duration of resuscitation > 60 min achieved ROSC. No difference in favorable neurological outcome in patients surviving to discharge was found (prehospital ROSC 84% vs. refractory OHCA 86%; p = 0.7). Conclusions Survival after refractory OHCA with ongoing CPR at hospital arrival was significantly lower than among patients with prehospital ROSC. Despite a lower survival, the majority of survivors with both refractory OHCA and prehospital ROSC were discharged with a similar degree of favorable neurological outcome, indicating that continued efforts in spite of refractory OHCA are not in vain and may still lead to favorable outcome even without eCPR.